2010
DOI: 10.1111/j.1346-8138.2010.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis treated with narrow-band ultraviolet B

Abstract: A 58-year-old man had widespread multiple erythemas that had been untreated for 20 years. The cutaneous lesions increased in size for a year. Histopathological examination revealed increased number of large, dysplastic, histiocytic cells in the dermis; most of these cells tested positive for Langelin, CD1a and S-100 staining. The patient was diagnosed with Langerhans cell histiocytosis (LCH) and treated with narrow-band ultraviolet B (NB-UVB) radiation. The erythema improved after treatment, but the tumor rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In most patients with limited cutaneous disease, an expectant management usually is enough, but topical steroids can be used too in selected cases [9,10]. Isolated skin lesions may be surgically excised, while more extensive skin disease might be managed with psoralen-uVA phototherapy, photodynamic therapy or topical nitrogen mustard [6,[11][12][13][14]. Localized bone lesions are managed with curettage, for diagnostic and therapeutic proposes, intralesional steroids, or low-dose radiation [15].…”
Section: Resultsmentioning
confidence: 99%
“…In most patients with limited cutaneous disease, an expectant management usually is enough, but topical steroids can be used too in selected cases [9,10]. Isolated skin lesions may be surgically excised, while more extensive skin disease might be managed with psoralen-uVA phototherapy, photodynamic therapy or topical nitrogen mustard [6,[11][12][13][14]. Localized bone lesions are managed with curettage, for diagnostic and therapeutic proposes, intralesional steroids, or low-dose radiation [15].…”
Section: Resultsmentioning
confidence: 99%
“…Suspected causative agents include infectious agents and immunodysfunction that give rise to abnormal proliferation of histiocytes. Related lymphocyte infiltration, cytokines and genetic factors have also been reported to be associated with the pathogenesis of eosinophilic pseudotumors in visceral organs . One pediatric study reported a rate of liver involvement of 15.6% in 217 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment strategies depend on the patients' age and the size of the pseudotumors. Narrow‐band ultraviolet B has been attempted as a treatment option for cutaneous LCH that is proven successful . Treatments for pulmonary LCH include cigarette‐smoking cessation, the use of steroids and lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations